Correlation between serum ferritin level and liver function tests in thalassemic patients receiving multiple blood transfusions - Asif, Mahmood; Manzoor, Zahid; Farooq, Muhammad Shehzad; Kanwal, Amama; Shaheen, Uzma; Munawar, Shaukat Hussain; Khan, Imran Ahmad; Aziz, Abdul (International Journal of Research in Medical Sciences, 2017)
Background:Multiple blood transfusions are the mainstay of thalassemic patients in order to combat the severe anemia. These frequent blood transfusions result in the excessive iron deposition, leading to multiple injuries to a variety of organs in the body. In response to these injuries, the levels of various enzymes are disturbed. The whole phenomena usually involve the interrelation of one parameter with some other. The present study aimed to estimate the levels of serum ferritin and hepatic enzymes and to find out any possible correlation between them in thalassemic patients receiving multiple blood transfusions. Methods:A total number of 90 thalassemic patients of both sexes ranging from 10-15 years, receiving multiple blood transfusions were included in the present study. Blood samples from all the patients were withdrawn and analyzed for the values of serum ferritin, hemoglobin and hepatic enzymes (serum alanine transaminase, serum aspartate transaminase, serum alkaline phosphatase). Pearson correlation coefficient was applied to observe correlation between serum ferritin level and hepatic enzymes. A P value of ≤0.05 was considered statistically significant. Results:The overall values of serum ferritin, and hepatic enzymes (serum Alanine Transaminase, serum Aspartate Transaminase, serum Alkaline Phosphatase) were remarkably increased than their normal values. However, hemoglobin level was considerably decreased in thalassemic patients. A weak positive insignificant correlation was observed between serum ferritin with hepatic enzymes and hemoglobin in thalassemic patients. Conclusion:Multiple blood transfusions cause iron overload in the body, which in turn, lead to increased serum ferritin levels in thalassemic patients. High levels of hepatic enzymes are somewhat correlated to serum ferritin concentration. However, the exact reason of elevated levels is still unclear. Further detailed studies should be conducted in order to identify the exact mechanism behind this and to search for the promising correlations of various parameters in thalassemic patients receiving multiple blood transfusions.